Analysis of the Bankruptcy Probability of Selected Companies Listed on the Warsaw Stock Exchange and Operating in Ukraine - Kondej, Magdalena (Metody Ilościowe w Badaniach Ekonomicznych, 2025)
The aim of the research was to assess the bankruptcy risk of three agribusiness companies listed on the Warsaw Stock Exchange and operating in Ukraine during the 2019-2023 COVID-19 pandemic and war. An Edward Altman discriminant analysis was carried out, along with an analysis of selected financial ratios. The results of the financial analysis of Astarta Holding N.V., KSG Agro S.A., and Ovostar Union N.V. from 2019 to 2023 reveal differing trends.